Effectiveness of Instructional Program Regarding Health Protective Behaviors for Women with Gestational Diabetes on Pregnancy Outcome in Primary Health Care Centers and Maternity Hospital at Baghdad City - Sagdh Hameed Kareem; Iqbal Majeed Abbas (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background:- Diabetes is a chronic disease in which pregnant with gestational Diabetes require lifelonghealth Protective Behaviors for Effective on Pregnancy OutcomeMethods: descriptive research design group Pre test used to determine the Effectiveness of InstructionalProgram Regarding Health Protective Behaviors for Women with Gestational Diabetes on PregnancyOutcome in Primary Health Care Centers and Maternity Hospital at Baghdad City.Methodology: descriptive research -l study conducted from 17th October 2020 to 30th January 2021,purposive sample Consisted of 50 pregnant women with gestation diabetic were selected from (4) primaryhealth centers, and tow from Al karkh department, and another Two from Al Rusafa in Baghdad City. Andselected from (4) Maternity Hospital Two from Al karkh department, and another Medical City Department.Results : The present study reports that the highest percentage (29%) of study sample is at age group rangingbetween (40 – 44) years old, with mean and SD = 32.38±7.22 years) the study sample was graduated fromSecondary school graduate, while the lowest percentage (9% ) were Neither read nor write This result wasin agreement by a study who reported that a majority of pregnant women (65.5%) indicated that pregnantwomen should receive on the education and The highest percentage (30%) of study sample was governmentof self employed while the lowest percentage (16 %) of study sample were .